2021
DOI: 10.1159/000520716
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient Can Predict Therapy Response of Hepatocellular Carcinoma to Transcatheter Arterial Chemoembolization

Abstract: Aim: The goal of this meta-analysis was to assess the apparent diffusion coefficient (ADC) as a pre- and posttreatment (ΔADC) predictive imaging biomarker of response to transcatheter arterial chemoembolization (TACE) in patients with hepatocellular carcinoma (HCC). Methods: SCOPUS database, EMBASE database and MEDLINE library were scanned for connections between pre- and posttreatment ADC values of HCC and response to TACE. Six studies qualified for inclusion. The following parameters were collected: authors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…ADC has been proven to have good diagnostic performance in the identification of benign and malignant lesions such as the brain, thyroid, pancreas, and uterus (38)(39)(40)(41)(42). In addition, ADC has also been confirmed in other studies to better predict the response evaluation of liver cancer, nasopharyngeal cancer, colon cancer with liver metastasis after treatment (43)(44)(45). Whether the ADC value can better distinguish benign and malignant ovarian or appendages is different in some previous studies (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…ADC has been proven to have good diagnostic performance in the identification of benign and malignant lesions such as the brain, thyroid, pancreas, and uterus (38)(39)(40)(41)(42). In addition, ADC has also been confirmed in other studies to better predict the response evaluation of liver cancer, nasopharyngeal cancer, colon cancer with liver metastasis after treatment (43)(44)(45). Whether the ADC value can better distinguish benign and malignant ovarian or appendages is different in some previous studies (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Both minimum and mean ADC values predicted treatment response in patients with locally advanced rectal cancer before neoadjuvant chemoradiation treatment (41). A recent meta-analysis showed that alterations between pre-and post-treatment ADC can identify responders to TACE in HCC (42).…”
Section: Discussionmentioning
confidence: 99%
“…There are no established imaging markers used for the prediction of TACE response. However, the delta of ADC values on MRI imaging higher than 20% facilitates early objective response to treatment [ 86 , 87 ]. To assess the presence of residual tumours, contrast-enhanced ultrasound can also be used.…”
Section: Tacementioning
confidence: 99%